Isolation and some basic characteristics of lactic acid bacteria from beetroot (Beta vulgaris L.) —A preliminary study - Setayesh Zamanpour; Reza Rezvani; Ali Jafarzadeh Isfahani; Asma Afshari (jurnal1, 2023)
The carbohydrate content of fruit and vegetable juices has made them a suitable environment for the growth of lactic acid bacteria. Various studies have shown that beetroot can be a good substrate for the production of probiotic drinks for consumers. Therefore, this study was performed to isolate and identify lactic acid bacteria from beetroot juice. Beetroot juice was prepared from two kilograms of washed beetroot with a cold press. Sterile samples of beetroot juice were first enriched in MRS broth and then cultured on MRS agar. Gram and catalase tests were used for the initial detection of lactic acid bacteria. Then, to identify the species of lactic acid bacteria, biochemical confirmation tests such as the melting of gelatin, and the growth of bacteria has been studied in the ideal condition that is 15-45° C, sugars fermentation, gas production from glucose, and growth in at different concentrations of salt were performed. The final verification of species was done using polymerase chain reaction-amplified 16S rRNA-specific DNA. All isolates formed creamy white round colonies on MRS agar medium, were gram-positive, were able to grow in anaerobic conditions, and were also rod-shaped and catalase-negative. Based on biochemical tests, four types of lactic acid bacteria (Lactobacillus plantarum, Lactobacillus helveticus, Lactobacillus salivarius, and Lactobacillus acidophilus) were identified. The findings of this study indicated the presence and diversity of lactic acid bacteria in beet juice, which can be a potential platform for the production of probiotic beetroot juice as a non-dairy product.